2020
DOI: 10.3390/su12229729
|View full text |Cite
|
Sign up to set email alerts
|

Application of Biostimulants Containing Amino Acids to Tomatoes Could Favor Sustainable Cultivation: Implications for Tyrosine, Lysine, and Methionine

Abstract: Tomato (Solanum lycopersicum L.) is one of the most important crops worldwide as per its production and the surface cultivated. The use of biostimulant products plays a fundamental role in mitigating the negative effects of climate change and reducing the use of conventional fertilizers. Many of these products are formulated with amino acids (AAs). This study was conducted to elucidate the effects of the foliar application of tyrosine (Tyr) (15 mM), lysine (Lys) (15 mM), methionine (Met) (15 mM), and a Tyr + L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
1
14
1
Order By: Relevance
“…They may contain protein hydrolysates, humic substances, algal and botanical extracts, inorganic compounds (e.g., Si), growthpromoting bacteria, mycorrhizal fungi (D'Addabbo et al, 2019;Cozzolino et al, 2020), amino acids, chitin, chitosan, vitamins, and poly-and oligosaccharides (Bulgari et al, 2015). The beneficial effects of biostimulants are not associated with their macro-and micronutrient composition but rather with their content of activating compounds, like endogenous hormones, small peptides, free amino acids, phenolics, and triacontanol (Ertani et al, 2014;Yakhin et al, 2017), which may affect plant metabolisms by triggering glycolysis enzyme activities, the Krebs cycle, and nitrate assimilation (Ertani et al, 2009;Colla et al, 2015Colla et al, , 2017Yakhin et al, 2017;Palumbo et al, 2018;Sandhu et al, 2018;Alfosea-Simón et al, 2020;Cozzolino et al, 2020;Francesca et al, 2020). On the other hand, if their biological activity depends on the presence of natural plant hormones, they ought to be classified as plant growth regulators (Bulgari et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They may contain protein hydrolysates, humic substances, algal and botanical extracts, inorganic compounds (e.g., Si), growthpromoting bacteria, mycorrhizal fungi (D'Addabbo et al, 2019;Cozzolino et al, 2020), amino acids, chitin, chitosan, vitamins, and poly-and oligosaccharides (Bulgari et al, 2015). The beneficial effects of biostimulants are not associated with their macro-and micronutrient composition but rather with their content of activating compounds, like endogenous hormones, small peptides, free amino acids, phenolics, and triacontanol (Ertani et al, 2014;Yakhin et al, 2017), which may affect plant metabolisms by triggering glycolysis enzyme activities, the Krebs cycle, and nitrate assimilation (Ertani et al, 2009;Colla et al, 2015Colla et al, , 2017Yakhin et al, 2017;Palumbo et al, 2018;Sandhu et al, 2018;Alfosea-Simón et al, 2020;Cozzolino et al, 2020;Francesca et al, 2020). On the other hand, if their biological activity depends on the presence of natural plant hormones, they ought to be classified as plant growth regulators (Bulgari et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Farhangi-Abriz and Ghassemi-Golezani 28 obtained similar results to our study on soybean. Alfosea-Simon et al, on the other hand, showed that giving amino acids such as methionine, lysine, and tyrosine exogenously to tomatoes reduced the harmful effects of salt stress in their study 29 .…”
Section: Resultsmentioning
confidence: 91%
“…AlfoseaSimon et al ., (2020) on the other hand, showed that giving amino acids such as methionine, lysine, and tyrosine exogenously to tomatoes reduced the harmful effects of salt stress in their study. 33…”
Section: Resultsmentioning
confidence: 99%
“…Alfosea-Simon et al, (2020) on the other hand, showed that giving amino acids such as methionine, lysine, and tyrosine exogenously to tomatoes reduced the harmful effects of salt stress in their study. 33 The changes in the Raman shift are a sign of molecular structure change in the plant we measured. As the number of oxidative stress products increases with the increasing salt levels, the Amide I band positions 34 and the level of proteins during stress change.…”
Section: Biochemical Analysis Using Raman Spectroscopymentioning
confidence: 92%